On the taxonomy of the genus Pseudacronicta Kononenko, 2001 (Lepidoptera, Noctuidae, Acronictinae): the identity of Acronicta omihsiensis Draeseke, 1928 - Kiss, Ádám (Zootaxa, 2020)
The genus Pseudacronicta was erected, in the noctuid subfamily Acronictinae by Kononenko (2001) as a monotypical genus. Pseudacronicta curiosa Kononenko, 2001 (Figs 2, 3), the type species of this genus, externally resembles Acronicta pulverosa Hampson, 1909 (Fig. 7) and A. pruinosa Guenée, 1852 (Fig. 8) (subgenus Plataplecta Butler, 1878). However, its wing pattern and structure of genitalia differ (Kononenko 2001). On the basis of habitus, P. curiosa appears more similar to Acronicta jozana Matsumura, 1926 (Fig. 6) (subgenus Hyboma Hübner, [1820] sensu Kononenko 2010) than the above mentioned species, but differs from them in the reduced basal dash, linear tornal streak located between the medial and postmedial lines, occasionally continuing between the antemedial and medial lines as a broken, sometimes reduced black line and the occasionally fused basal dash and tornal streak.